Microleakage of two self-adhesive cements in the enamel and dentin after 24 hours and two months. - Zahra Jaberi Ansari; Mojdeh Kalantar Motamedi (Tehran University of Medical Sciences, 2014)
Microleakage is a main cause of restorative treatment failure. In this study, we compared occlusal and cervical microleakage of two self-adhesive cements after 24 hours and two months.In this in-vitro experimental study, class II inlay cavities were prepared on 60 sound human third molars. Composite inlays were fabricated with Z100 composite resin. The teeth were randomly assigned to six groups. RelyX-Arc (control), RelyX-Unicem and Maxcem were used for the first three groups and specimens were stored in distilled water at 37°C for 24 hours. The same cements were used for the remaining three groups, but the specimens were stored for 2 months. The teeth were subjected to 500 thermal cycles (5°C and 55°C) and immersed in 0.5% basic fuchsin for 24 hours and then sectioned mesiodistally and dye penetration was evaluated in a class II cavity with occlusal and cervical margins using X20 magnification stereomicroscope. Data were analyzed using Kruskal Wallis and Mann-Whitney U tests.After 24 hours, cements had significant differences only in cervical margin microleakage (P=0.0001) and microleakage of RelyX-Unicem and Maxcem was significantly more than that of RelyX-Arc (both P=0.0001). Cervical microleakage in RelyX-Unicem and Maxcem was greater than occlusal (P=0.0001 and P=0.001, respectively). Microleakage was not significantly different between the occlusal and cervical margins after 2 months.Cervical microleakage was greater than occlusal in RelyX-Unicem and Maxcem after 24h. The greatest microleakage was reported for the cervical margin of RelyX-Unicem after 24 hours.